واقع تبني المؤسسات العمومية الجزائرية لأبعاد المسؤولية الإجتماعية في ظل جائحة كورونا. "مؤسسة سوناطراك نموذجا". - شامي, صليحة; بسي, نعيمة (جامعة الوادي - University of Eloued, 2023)
هدفت هذه الدراسة لتبيان مدى مساهمة المؤسسات العمومية الجزائرية في التصدي للأزمات في إطار المسؤولية الإجتماعية ، وذلك بمحاولة تقييم مدى تبني مؤسسة سوناطراك لأبعاد المسؤولية الإجتماعية في ظل جائحة كورونا ، من خلال عرض حجم مساهماتها خلال الأزمة ، توصلت الدراسة إلى أن سوناطراك أثبتت أنها مؤسسة إجتماعية متضامنة و مواطنة و ذلك من خلال الأعمال الخيرية التي قامت بها ، إلاّ أن دورها لم يصل بعد إلى المسؤولية المنوطة بها ، فدورها لا يزال محدودا و مساهمتها كانت رمزية و جزئية ، إضافة إلى محدودية مجالات استثماراتها التنموية. The purpose of this study is to demonstrate the extent of the contribution of Algerian public institutions in responding to crises within the framework of social responsibility and in an attempt to evaluate the extent to which the Sonatrach Foundation adopts the dimensions of social responsibility in the light of the Corona pandemic,by presenting the size of its contributions during the crisis, the study concluded that Sonatrak has proven itself to be a solidary and citizen social institution through the charitable works it has carried out,However, her role has not yet reached the responsibility assigned to her, so her role is still limited and her contribution was symbolic and partial, in addition to the limited areas of her developmental investments.
The reality of the Algerian public institutions' adoption of the dimensions of social responsibility in light of the Corona pandemic. Sonatrach Foundation as a model
مقال
Keywords: المسؤولية الإجتماعية للشركات ; أبعاد المسؤولية الإجتماعية ; مؤسسة سوناطراك ; جائحة كورونا